The Okanagan Charter: Evolution of Health Promotion in Canadian Higher Education - Squires, Vicki; London, Chad (Canadian Journal of Higher Education, 2022)
This paper traces the history of health promotion on campuses, including the initial attempts at providing oversight over student behaviour to the increased need for further supports after the influx of World War II veterans onto campuses, to the focus on providing a much broader range of supports that consider well-being from a holistic stance. We describe the current context where campuses are beginning to take a more intentional and organized approach to well-being across Canada; for context, we have included a description of our recent study that explores impactful practices on Health Promotion campuses that have implemented the Okanagan Charter (2015) (Authors, in press). The immediate context with the evolving global pandemic, reliance on online learning, emphasis on diversity and increasing access for all will also be explored. Lastly, we suggest future directions for campuses to take to address the current pressures and how a network of campuses engaged in well-being efforts who are employing whole systems approaches can be a hopeful model for ensuring well-being on Canadian campuses in the future.